Preparing First Year Engineering Students to Become Engineers: The Impact of an â€œIntroduction to Engineeringâ€ Course - Samsuri, Nur Shahira; Yusof, Khairiyah Mohd; Aziz, & Azmahani Abdul (Journal of Technical Education and Training, 2017)
The purpose of this research is to investigate the effectiveness of the â€œIntroduction to Engineeringâ€ (ITE) course in supporting first year engineering students to transition from school to university in preparing them to be good engineers for the 21st century.  To ensure an effective learning environment in the ITE course, the How People Learn (HPL) framework was utilised as a basis for the design of the course.  To determine the suitability and the impact of the course on the first year students, an exploratory qualitative research design was used where the interview data were gathered via interviews on 20 first year Chemical Engineering students at a university in Malaysia at the beginning, the middle and the end of the semester.  Thematic analysis technique was carried out to identify what students had gained throughout the course. From the analysis, three important themes emerged; (i) engineering knowledge; (ii) professional skills; and (iii) attitude. From the analysis of the data, it can be concluded taht the â€œIntroduction to Engineeringâ€ course has a positive impact on studentsâ€™ understanding of engineering, professional skills and attitude, that are essential for higher order thinking skills in preparation for them to be future engineers.